Akuntansi Keperilakuan, Landasan Akuntansi Keperilakuan Dalam Perspektif Islam - Septiarini, Dina Fitrisia (UNIVERSITAS NEGERI SURABAYA, 2013)
AbstractBehavioral accounting is the branch of accounting that studies the relationship between human behavior with the accounting system Accounting utilities or tools are used by humans in the activity and life. How human behavior in performing the accounting should refer to the purpose of human existence the Earth as God's people, so that information systems are formulated in Accounting should help people carry out the mandate of God in delivering the correct report about an institution and participated in enforcing the Sharia in an enterprise that is reported. Human behavior in berakuntansi should be based on the source of truth and value accounting of Shariah that are sourced from Almighty God according to the pragmatism of unity embraced Islam. God Almighty be the source of truth, source of guidance and guidelines that will guide humanity in all aspects of life including report accountability when humans perform process accounting